Revision of the conservation status and assessment of the Green Status of the Parana Antwren Formicivora acutirostris with management proposals - Bornschein, Marcos R. [UNESP]; Sandretti-Silva, Giovanna [UNESP]; Sobotka, Daiane D.; Corrêa, Leandro; Reinert, Bianca L.; Vannucchi, Fabio Stucchi [UNESP]; Pie, Marcio R. (Cambridge University Press (CUP), 2024)
Assessing the conservation status of a species is important for designing effective conservation measures. Consequently, it is often vital to review it to update biodiversity management initiatives. The Parana Antwren Formicivora acutirostris is a bird found in pioneering formations (coastal marshes) of Brazil's southern flood plains. It is considered threatened in Brazil but near threatened globally. In 2007, its distribution, habitat, and population size were estimated based on aerial photographs from 1978 and 1980. Since the species is threatened and occupies a small area across a region under pressure, we aimed to reassess its conservation status and assess its Green Status. We compiled new records, conducted new density estimates, and compared them with the previous mapping with satellite imagery to estimate the current distribution in terms of extent of occurrence (EOO), area of occupancy (AOO), area of habitat (AOH), habitat loss, and population size, and review its conservation status. The species is distributed across 10 populations, including two new populations further south. We estimated the EOO at 26,655 km², AOO at 320 km², AOH at 41 km², and the population as 6,285 mature territorial individuals. The previously mapped AOH decreased by 15.35 km² due to ecological succession. The loss of habitat due to invasion by exotic grasses is the main anthropogenic impact. We recommend that the species be considered Vulnerable. The Green Status indicates that the Conservation Legacy of actions taken thus far and the Conservation Dependence of ongoing actions are inefficient due to their small scales, but it highlights the importance of future actions for species conservation. We propose the establishment of exotic-free zones as small areas with a significant amount of minimally invaded environments, which we suggest as priority areas for the conservation of the species due to their cost-effective management potential. We also propose assisted colonisation to enhance its long-term conservation.
Keywords: Area of habitat; Assisted colonisation; Biological invasion; Ecological succession; Urochloa arrecta